Assessment of Factors Affecting the Implementation of Projects in the Field of Green Logistics in Poland in the Perspective of the Sustainable Development Concept - Motowidlak, Urszula (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The aim of the article is to assess the essential factors determining the implementation of Green Logistics projects for the sustainable development of the logistics potential of Polish enterprises. The article discusses the strategic role of business in achieving goals in the field of sustainable development of logistics processes. It is the result of international conventions and the obligations imposed on the state and enterprises arising from these conventions. Based on literature studies and analysis of existing data, five basic categories of factors determining the development of Green Logistics projects were identified. Within these areas, specific actions were identified as important for entrepreneurs. They were then assessed as a result of an in‑depth questionnaire interview. Special attention was paid to the need for implementing technological solutions, which is crucial for the development of Green Logistics. It was emphasised that Green Logistics can be an important element of the global economic balance.